Eco-Spirituality and Nationhood in Indunisiya Al-Badiʿah By Kh. Abdullah Bin Nuh: An Ecocritical Study for SDGs - Minatur Rokhim; Ali Hasan Al Bahar; Darsita Suparno; Siti Sa'adah; Muhamad Ali Raaf Sanjani; Ashim Romadhony (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to analyze the poetry of Indunisiya al-Badiʿah by KH. Abdullah bin Nuh uses heuristic, hermeneutics, and ecocriticism approaches to uncover the synthesis of Islamic spiritual values, nationalism, and ecological awareness, and examine their relevance to the achievement of the Sustainable Development Goals (SDGs), especially SDG 4, SDG 13, and SDG 15. Theoretical framework: The theoretical framework of this research refers to ecocritical theories (Glotfelty, Buell, Garrard), which study the relationship between literature and the environment; Islamic spirituality theories (Nasr, Izutsu), which view nature as God's āyāt; and the SDGs framework, which guides the integration of sustainability values into literary works. Literature review: Literature review shows that Indonesian literature, such as the works of WS Rendra, Taufiq Ismail, and Emha Ainun Nadjib, has raised a lot of environmental issues. However, ecocriticism research on Arabic-Indonesian literature written by Islamic boarding school figures, especially KH. Abdullah bin Nuh is still very limited. The relevant literature affirms the role of literature as a means of ecological literacy, education for sustainable development, and preservation of cultural heritage, in line with SDG 4.7, SDG 13, SDG 15, and SDG 11. Methods: Interpretive qualitative approach through heuristic, hermeneutical, and ecocritical-contextual reading; primary data in the form of poetry texts, secondary data from theoretical literature; validation through theoretical and contextual triangulation. Results: The results of the study show that this poem utilizes the natural symbols of the archipelago, such as mountains, valleys, dhuha light, local flowers, animals, and water as a medium for ecospiritual da'wah and prophetic nationalism. Nature is positioned as a spiritual space that must be protected, with a message that is in line with SDG 4, SDG 13, and SDG 15. Implications: Showing the role of Arabic-Indonesian literature as an ecological education instrument based on religious values, supporting cultural strategies for the SDGs, and the preservation of intangible culture. Novelty: The first ecocritical analysis of the classic Arab-Indonesian works of Islamic boarding school scholars that integrate ecospirituality, nationalism, and global sustainability.